2018
DOI: 10.1021/acsphotonics.8b00899
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Degree of Optical Polarization above 80% in AlGaN-Based Deep-Ultraviolet LED with Moth-Eye Microstructure

Abstract: For the first time, an ultrahigh degree of optical polarization (DOP) of 81.8% in AlGaN-based deep ultraviolet LED (DUV-LED) operated at 286 nm has been experimentally demonstrated. The very high DOP was obtained by introducing the novel moth-eye microstructure fabricated on the backside of a sapphire substrate. Compared with conventional DUV-LED with a DOP of 64.7%, a significant 1.26-fold enhancement was obtained. It was worth mentioning that the DOP was accurately measured via self-built full spatial transv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 34 publications
0
32
0
Order By: Relevance
“…[ 65,66 ] Another example is the helical traveling‐wave nanoantenna, which enables the tunable polarization control by the optical spin–orbit interaction. [ 67 ] There are also nanostructures such as the moth eye, [ 68 ] which could improve the degree of optical polarization and then double the LEE of LED.…”
Section: Fundamental Mechanisms Of Nanoantenna‐enhanced Ledmentioning
confidence: 99%
“…[ 65,66 ] Another example is the helical traveling‐wave nanoantenna, which enables the tunable polarization control by the optical spin–orbit interaction. [ 67 ] There are also nanostructures such as the moth eye, [ 68 ] which could improve the degree of optical polarization and then double the LEE of LED.…”
Section: Fundamental Mechanisms Of Nanoantenna‐enhanced Ledmentioning
confidence: 99%
“…They were able to enhance the performance of 282 compared with conventional at sapphire substrate, by adopting NSL and wet etching mechanisms. In another report, Zhou et al demonstrated the effect of different sizes of cone-shaped-PSS on performance of UV LED emitting at 375 nm [446] . They noticed that TDDs are in a decreased trend associated with increasing pattern sizes and with the PSS filling factor.…”
Section: Device Fabricationmentioning
confidence: 99%
“…In their design, a conventional Al x Ga 1-x N-based LED is modified into a UV LED structure by utilizing the following features: Fig. 16 shows a moth-eye micro-arrays which was fabricated on the back of sapphire platform to significantly increase the LEE by weakening the total internal reflection (TIR) [447] . Consequently, a high degree of optical polarization (DOP) of 81.8% is obtained for DUV LED utilizing moth-eye micro-arrays, compared to a standard DUV LED of DOP of 64.7%.…”
Section: Device Fabricationmentioning
confidence: 99%
“…However, light will be reflected at the interface between media and will be absorbed by p - or n -type layers and electrodes. For AlGaN, the total reflection angle is only 26° 42 , thereby resulting in extremely low LEE. On the other hand, AlGaN materials with high Al content have significant optical anisotropy.…”
Section: Introductionmentioning
confidence: 99%